Cotton - Abdurakhmonov, Ibrokhim Y. (IntechOpen, 2022)
This book discusses the latest advances in cotton genetics and the biochemistry, physiology, bioinformatics, and genomics of the cotton plant. Chapters cover genomics and transcriptomics approaches to characterization and tagging of essential genes, novel transgenic tools to accelerate breeding against climate issues, abiotic and biotic stress pressures, biological control and machinery tools for cotton plant protection, cotton seed meal production, and sustainable and effective farming in the era of climate change and technological advance.